Effect of Working Conditions on Mental Health Health Personnel in the Covid-19 Pandemic - Stascia, Stefani; Pramono, Rudy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Healthcare workers face Covid-19 patients and are at risk of being exposed to the virus, they also work long shifts, with high workloads, and face logistical constraints. This study was conducted to determine the effect of working conditions on the mental health of healthcare workers during the Covid-19 pandemic. The purpose of this study is to determine the effect of the independent variables, which are working hours, workload, support from peers, support from supervisors, logistical support and occupational competence on the mediating variable which is working conditions, and to determine the effect of working conditions on the dependent variable of mental health. This research was conducted in Depok City, involving 162 health workers at SMC Hospital. Questionnaires were distributed using the google form application to collect data based on quota sampling, the questionnaire contained 58 questions using a Likert scale value 1 – 5. All data analysis used the PLS-SEM method with the results of the study stating that there was a positive impact between all independent variables on working conditions and there is a positive impact between the working conditions variable and mental health. It was also found that there is low predictive accuracy with low predictive relevance on the dependent variable of mental health, while the mediating variable working conditions has moderate predictive accuracy with high predictive relevance, so this research can be developed further to obtain an appropriate model. This research also has managerial implications as well as recommendations for further research.